2015
DOI: 10.1111/ijfs.12917
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure characteristics, functional parameters and in vitro protein digestion of pressure‐cooked soya bean flours with different amounts of water

Abstract: When a food product is cooked at high temperature with different proportions of water, the differential degradation that occurs in the molecular structure promotes changes in their functional characteristics. In this study, water and soya bean flour (dry base) were mixed in different ratios (3:1, 2:1, 1:1, 0.25:1 and 0:1) and pressure cooked at 130°C, 1.5 kg cm À2 for 30 min, cooled down to 40°C and air dried for 24 h. Protein changes due to thermal process were determined with the ATR-FTIR, as well as some fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…On the other hand, raw protein extracts from white bean and broad bean showed the lowest digestion values (80.59% and 82.35%, respectively), while chickpea and lentil showed 92.41% and 91.47%, respectively, that could be related to the absence of protease inhibitors and other seed components, as well as the possibly partial thermal denaturation of protease inhibitors during its processing. Previous reports have shown similar in vitro digestion values in thermal processed protein isolates (Hsu et al ., ; Ng & Ng, ), inferring that under such conditions there was an affective decrease on the protease inhibitors that are present in most legumes (Ma et al ., ; de la Rosa‐Millán et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…On the other hand, raw protein extracts from white bean and broad bean showed the lowest digestion values (80.59% and 82.35%, respectively), while chickpea and lentil showed 92.41% and 91.47%, respectively, that could be related to the absence of protease inhibitors and other seed components, as well as the possibly partial thermal denaturation of protease inhibitors during its processing. Previous reports have shown similar in vitro digestion values in thermal processed protein isolates (Hsu et al ., ; Ng & Ng, ), inferring that under such conditions there was an affective decrease on the protease inhibitors that are present in most legumes (Ma et al ., ; de la Rosa‐Millán et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…c). Other authors have found that thermal processing is positively correlated with protein denaturation as well as higher in vitro digestion (Krintiras et al ., ; de la Rosa‐Millán et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Protein digestibility is an important quality assessment in food. Compared with vegetable protein sources, A. platensis digestibility was 70%, which is higher than the value of 58% reported for soybean flour but lower than values reported by Caballero de la Peña for casein, whey protein‐concentrate and soybean‐maize germ protein isolate (98%, 90% and 86%, respectively). Compared with non‐animal sources, cyanobacteria digestibility was higher given the lack of fiber in the cell walls .…”
Section: Resultsmentioning
confidence: 99%